Syntheses, electrochemical and spectroelectrochemical properties of novel ball-type and mononuclear Co(II) phthalocyanines substituted at the peripheral and non-peripheral positions with binaphthol groups - Canlica, Mevlude; Booysen, Irvin Noel; Nyokong, Tebello (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Mononuclear cobalt phthalocyanine (CoPc) substituted at the non-peripheral Sand peripheral positions 9 with 1,1'-binaphthy1-8,8'-diol and ball-type dinuclear Co2Pc2 substituted at the non-peripheral 10 and peripheral 11 positions with the same substituent are reported. The complexes with 1,1'-binaphthol-bridges were prepared from the corresponding phthalonitriles 4-7. The effects of the position of substituent on spectral, electrochemical and spectroelectrochemical properties of these complexes were also explored. The mononuclear complexes 8 and 9 exhibited one metal reduction, one ring reduction and one ring oxidation. The redox properties of the ball-type complexes 10 and 11 exhibited two reduction processes assigned to [((CoPc-2)-Pc-I)(2)](2-)/[((CoPc-3)-Pc-I)(2)](4-) (I), ((COPc-2)-Pc-II)(2)/[((COPc-2)-Pc-I)(2)](2-) (II) and one oxidation process assigned to [((CoPc-2)-Pc-III)(2)](2+)/(CoPc-2)-Pc-II)(2) (III). The ball-type complexes are much easier to oxidize and more difficult to reduce than the corresponding monomers 8 and 9. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cobalt ball-type phthalocyanines; Non-peripheral and peripheral; phthalocyanines; Electrochemistry; Spectroelectrochemistry; GAS-SENSING PROPERTIES; CLAMSHELL; Chemistry; Crystallography